Clinical Features of Severe Malnutrition at the Pediatric Ward of Dr. Pirngadi Hospital Medan - Sabar Tuah Barus; Rohani Rani; Nuchsan U. Lubis; Endang D. Hamid; Sjarikat Tarigan (Indonesian Pediatric Society, 1990)
A retrospective study on severe malnutrition concerning children hospitalized at the Pediatric ward of Dr. Pirngadi Hospital, Medon from January 1 to December 31, 1988 was conducted. Patients less than five years old were included in this study. The purpose of this study was to know the incidence of severe malnutrition, its symptoms and signs, the immunization status, feeding pattern and socio-economic factors. Out of the 3370 hospitalized patients, 2453 (72. 78%) were children under five years old. Of these, 312 (12%) suffered from severe malnutrition. It consisted of marasmus 131 (41.9%), marasmic kwashiorkor 94 (30.1%) and kwashiorkor 87 (27.8%). The highest incidence was found in the age group of 0- 2 years (58%). Clinical manifestation of marasmus were old man face (131 or 100%), muscular hypotrophy (118 or 71.9%) and decreased subcutaneous fat (116 or 71.1%) in marasmic kwashiorkor children 46 or 50% had their hair easily picked out, 45 or 46.3% showed hyperpigmentation and 48 or 52% had pretibial edema in the kwashiorkor group 29 or 63% had moon face, 52 or 60.4% showed crazy pavement dermatosis, 77 or 51.3% had hepatomegaly and 87 or 48% pretebial edema. Moon face was seen in 29 (63%), crazy Pavement Dermatosis in 52 (60.4%), hepatomegaly in 77 (51.3%), and pretebial edema in 87 (48%) of kwashiorkor cases. The accompanying diseases were mostly diarrhea (95%) and bronchopneumonia (22%). Immunization status showed that BCG comprised 50.6%, while DPT III and OPV III in 13.7% and 10.5% respectively and measles only 0.64%. More than half (59.6%) of them were breast-fed up to 6 months. Most of the parents had elementary education, namely 66.6% of mothers and 52.2% fathers. The majority of the fathers worked as seasonal workers (57.3%). This study suggested that health problems, as well as socio-economic factors played an important role in the occurrence of severe malnutrition.